Influência da implantação de radares na ocorrência de acidentes de trânsito em Cuiabá - MT - Souza, Francisca Kaline Bezerra de (2018)
The theme of traffic accidents has been approached in the analyzes of articles, dissertations and theses of the Brazilian Universities and some foreign institutions, due to the great damages caused to the public coffers and mainly to their victims. The report published in May 2017 by the World Health Organization (WHO) indicates that Brazil has a rate of 23.4 traffic deaths per 100,000 inhabitants, and is the fourth country in the number of deaths due to accidents among the countries of the Americas In Mato Grosso, according to the Public Safety Statistical Yearbook of 2017, a total of 948 traffic casualty deaths were registered for the years 2015 and 2016, in the same period in Cuiabá, 164 deaths were registered. With 14 deaths per 100,000 inhabitants, the MT State is the fourth in number of accidents in the national ranking. The main cause of the most serious traffic accidents is the speeding of vehicles at the time of the collision, so speed control is an important instrument for reducing accidents and their severity. In order to curb the violation of this nature on public roads, the electronic surveillance system has been adopted, which, upon verifying the infraction, notifies the driver and penalizes him with a pecuniary fine and increase points in the driver's license, according to the classification of the offense committed. The electronic surveillance system that has been operating in Cuiabá since October 2014, is currently 148 monitored tracks, resulting in a total of 75 equipment (between electronic spikes, hybrid radar and fixed radar). According to the Secretariat of Urban Mobility, 396,545 fines were recorded in 2015, of which 83,260 were manual and 313,285 electronic, in 2016 were 241,711 fines, 41,525 manuals and 200,186 electronic. The analysis of the phenomenon of traffic accidents is only possible through the existence of a database, since information is an essential resource for any planning process. Based on the records of occurrences reported by the Emergency Department of the Public Security Secretariat of Mato Grosso and the Municipal Department of Urban Mobility of Cuiabá, through the combination of the use of geoprocessing tools and spreadsheets, it was possible to analyze the data, comparisons of the number of occurrences recorded before and after the radars, within a range of up to 1000 meters away from the equipment. Data analysis showed that in the entire city of Cuiabá, between the years 2013 and 2016 there was an increase in the number of traffic accidents. The presence of radars in the main streets and avenues of the city of Cuiabá significantly influenced the reduction of accidents in its vicinity. Excerpts from tracks monitored distant more than 1000 meters of some radar had a significant increase in the number of accidents, as well as in unmonitored ways. In the stretches up to 1000 meters distant from some radar, the accidents with victims, as well as the crunches, presented reduction more than the accidents without victims. Analysis of accident occurrence rates demonstrate that the monitoring and surveillance radars are effective in the city of Cuiabá.